A Study of Cyber-Attacks on Healthcare Sector in the US during Covid-19 and Post Covid-19 Periods: Some Lessons Learnt - Premanand Narasimhan; Dr.N.Kala (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2024)
Cybercriminals are jumping to utilize the pandemonium and confusion about this unprecedented epidemic to spread a “virus” in the digital realm for their nefarious purposes. Cybercriminals use emergencies such as 2019-nCov to get people to make decisions quickly. Adversaries are keenly aware of these challenges and the opportunities for abusing this situation to their advantage, spreading the virus under the guise of SARS-CoV-2 (COVID-19), causing an “online infection” of millions. Prolific and opportunistic criminal syndicates have taken advantage of the Covid 19 coronavirus pandemic to launch a variety of cyber-attacks which is staggering in the health care sector. Such attacks are complex and co-ordinated. This has resulted in widespread disruption in the health care sector. National and international regulatory bodies have emphasized that the health care sector needs to protect themselves from cyber-attacks considering the fact that the criminal syndicates capitalize the vulnerabilities in the health care sector. This paper focuses on the identification of different cyber-attacks that have targeted the health care sector during covid and post-covid scenarios. This paper also discusses the type of entity, type of breach, number of individuals affected, location of the attack and state-wide health care sector being affected. This paper further identifies the lessons to be learnt in order to protect the resources from future attacks.
Keywords: cyber-attacks; healthcare; covid -19; post-covid; US Healthcare